1999
DOI: 10.3904/kjim.1999.14.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Chlormethiazole , a Sedative , against Acetaminophen - Induced Liver Injury in Mice

Abstract: ObjectivesThe hepatotoxicity of acetaminophen is not a result of the parent compound but is mediated by its reactive metabolite N-acetyl-p-benzoquinone imine. Cytochrome P4502E1 (CYP2E1) is the principal enzyme of this biotransformation, which accounts for approximately 52% of the bioactivation in human microsomes. Recently, chlormethiazole, a sedative drug, is reported to be an efficient inhibitor of CYP2E1 activity in human beings. In this study we wished to evaluate whether chlormethiazole, an inhibitor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Chlormethiazole (CMZ), a drug used for alcohol withdrawal and agitation, and an efficient inhibitor of CYP2E1 activity, 26 was used to try to prevent the Jo2 agonist Fas antibody-induced liver injury found in Pyrtreated mice. Mice were divided into Sal (n ϭ 3), Pyr/Jo2 (n ϭ 6), and Pyr/Jo2 plus CMZ (n ϭ 16) groups, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Chlormethiazole (CMZ), a drug used for alcohol withdrawal and agitation, and an efficient inhibitor of CYP2E1 activity, 26 was used to try to prevent the Jo2 agonist Fas antibody-induced liver injury found in Pyrtreated mice. Mice were divided into Sal (n ϭ 3), Pyr/Jo2 (n ϭ 6), and Pyr/Jo2 plus CMZ (n ϭ 16) groups, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…They demonstrated that chlormethiazol was able to prevent liver injury in mice resulting in the survival of mice administered a high dose (500 mg/kg) of acetaminophen. A greater than 50 % death rate was observed in mice that were not co-administered chlormethiazol (Lee et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…CMZ is thought to be a specific inhibitor of CYP2E1, 15 and it has been shown to ameliorate CYP2E1-mediated liver damage in rats treated chronically with ethanol, 16 in mice treated with acetaminophen 17 or mice treated with Jo2/pyrazole. 12 CYP2E1-knockout mice have been used in studies on toxicity of acetaminophen, 18 carbon tetrachloride, 19 chloroform, 20 and alcohol.…”
Section: Lps Directly Causes Liver Injury By Mechanisms Involving Infmentioning
confidence: 99%